2012
DOI: 10.4103/0253-7613.96307
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of reserpine-induced orofacial dyskinesia and catalepsy by Nardostachys jatamansi

Abstract: Context:Reserpine-induced orofacial dyskinesia is an animal model of tardive dyskinesia which may be associated with neurodegeneration and free radical damage.Aim:The aim was to assess the neuroprotective potential and in vivo antioxidant status of alcoholic extract of roots and rhizomes of Nardostachys jatamansi (ANJ) and its triterpenes (TNJ) in reserpine-induced orofacial dyskinesia.Materials and Methods:In the present study, repeated treatment with reserpine (1.0 mg/kg) on each other day for a period of 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…www.ajpp.in (Nair et al, 2007;Patil et al, 2012). We observed haloperidol significantly increases catalepsy in mice.…”
Section: Tacrine Induced Tongue Protrusionsupporting
confidence: 50%
See 1 more Smart Citation
“…www.ajpp.in (Nair et al, 2007;Patil et al, 2012). We observed haloperidol significantly increases catalepsy in mice.…”
Section: Tacrine Induced Tongue Protrusionsupporting
confidence: 50%
“…Nardostachys jatamansi (NJ) commonly named as jatamansi belongs to family Valerianaceae shows presence of terpenes, saponins, glycosides, flavonoids, tannins and phenolic compounds which are responsible for synergistic reduction in oxidative stress via inhibition of mono-amine oxidase enzymes (Patil et al, 2012). Sequiterpines, mainly Jatamansone, and coumarins are main active constituents present in NJ including other sequiterpines such as Alpha-patcho-ulense, Betaeudesemo, beta-sitosterol, elemol, angelicin, jatamansin, jatamansinol, calarene, beta-atchoulense, n-hexaco-sanyl, nhexacosane, Oroselol, valeranal, valeranone, seychelane, nardostachnol, nardostachone and also volatile oil (Nakoti et al, 2017;Mishra et al, 2014).…”
Section: Nardostachys Jatamansimentioning
confidence: 99%
“…Animal experiments studied candidate pathways involved in TD development on the level of functional perturbations due to treatment with antipsychotics. Inflammation ( Bishnoi and Boparai 2012 ; Grover et al, 2013 ; Thakur et al, 2015 ; Datta et al, 2016 ; Peroza et al, 2016 ; Sonego et al, 2018 ; Soung et al, 2018 ; Wang et al, 2021a ) and oxidative stress defense ( Patil et al, 2012 ; Grover et al, 2013 ; Nade et al, 2013 ; Thakur et al, 2015 ; Wang et al, 2015 ; Datta et al, 2016 ; Schaffer et al, 2016 ; Samad and Haleem 2017 ; Dhingra et al, 2018 ; Sonego et al, 2018 ; Soung et al, 2018 ; Tsai et al, 2019 ; Wang et al, 2021a ) pathways were among the most studied ones. Accordingly, different antioxidants were tested as potential agents for the treatment of TD.…”
Section: Preclinical Studies Of Tardive Dyskinesia Developmentmentioning
confidence: 99%
“…Accordingly, different antioxidants were tested as potential agents for the treatment of TD. Many studies showed decreased levels of catalase (CAT), superoxide dismutase (SOD), and glutathione (GSH), either in their quantity or antioxidant capacity, upon treatment with haloperidol ( Grover et al, 2013 ; Thakur et al, 2015 ; Datta et al, 2016 ; Samad and Haleem 2017 ; Dhingra et al, 2018 ; Sonego et al, 2018 ; Tsai et al, 2019 ; Wang et al, 2021a ), reserpine ( Patil et al, 2012 ; Nade et al, 2013 ; Wang et al, 2015 ; Soung et al, 2018 ) or fluphenazine ( Schaffer et al, 2016 ). Studies have also shown that a plethora of cytokines are elevated upon treatment with antipsychotics, such as TNF- α ( Bishnoi and Boparai 2012 ; Grover et al, 2013 ; Thakur et al, 2015 ; Datta et al, 2016 ; Peroza et al, 2016 ; Sonego et al, 2018 ; Soung et al, 2018 ; Wang et al, 2021a ), IL-1 β ( Grover et al, 2013 ; Thakur et al, 2015 ; Datta et al, 2016 ; Peroza et al, 2016 ; Sonego et al, 2018 ; Wang et al, 2021a ), IL6 ( Datta et al, 2016 ; Peroza et al, 2016 ; Sonego et al, 2018 ; Soung et al, 2018 ; Wang et al, 2021a ), and IFN- γ ( Peroza et al, 2016 ).…”
Section: Preclinical Studies Of Tardive Dyskinesia Developmentmentioning
confidence: 99%
“…Evidence from many experimental and clinical studies also suggests that neuroleptics induce oxidative stress and cell death. Even lipid peroxidation byproducts in blood and cerebrospinal fluid are increased in patients with tardive dyskinesia [7,8].…”
Section: Introductionmentioning
confidence: 99%